Coercive diplomacy, sanctions and international law - Ronzitti, Natalino (Brill Nijhoff, 2016)
This volume explores sanctions as instruments of coercive diplomacy, delving into theoretical arguments and combining perspectives from international law and international relations scholars and practitioners. Primary questions include the compatibility and legitimacy of sanctions regimes, enforcement measures, including the role of sanctions committees, the practice of circumventing sanctions, and the relation with the ICC proceedings. Legal and institutional aspects of the practice of the European Union are addressed. The extraterritorial effects of national legislation implementing sanctions imposed by individual States are investigated. A focus is on the impact of sanctions on non-State actors. The connections with the protection of human rights and the adverse impact on individual rights are considered. The implementation of sanctions is addressed in view of their legal limitation and the concept of proportionality, their consequences upon existing treaties and contracts, their effectiveness, and their strategic implications.